Interleukin (IL)-23 stimulates IFN-γ secretion by CD56bright natural killer cells and enhances IL-18-driven dendritic cells activation - Ziblat, Andrea (2018)
Interleukin (IL)-23 is a member of the IL-12 family of cytokines that, as the other members of this family, is secreted by monocytes, macrophages, and dendritic cells (DC) upon recognition of bacterial, viral, and fungal components. IL-23 is critical during immunity against acute infections, and it is also involved in the development of autoimmune diseases. Although immunoregulatory effects of IL-23 on mouse natural killer (NK) cells have been described, the effect of IL-23 on human NK cells remains ill-defined. In this study, we observed that monocytes stimulated with LPS secreted IL-23 and that blockade of this cytokine during monocyte and NK cell coculture led to a diminished production of IFN-γ by NK cells. Accordingly, rIL-23-induced NK cell activation and stimulated IFN-γ production by CD56bright NK cells. This effect involved MEK1/MEK2, JNK, PI3K, mammalian target of rapamycin, and NF-κB, but not STAT-1, STAT-3, nor p38 MAPK pathways. Moreover, while NK cell-mediated cytotoxicity remained unaltered, antibody-dependent cellular cytotoxicity (ADCC) was enhanced after IL-23 stimulation. In addition, IL-23 displayed a synergistic effect with IL-18 for IFN-γ production by both CD56bright and CD56dim NK cells, and this effect was due to a priming effect of IL-23 for IL-18 responsiveness. Furthermore, NK cells pre-stimulated with IL-18 promoted an increase in CD86 expression and IL-12 secretion by DC treated with LPS, and IL-23 potentiated these effects. Moreover, IL-23-driven enhancement of NK cell "helper" function was dependent on NK cell-derived IFN-γ. Therefore, our results suggest that IL-23 may trigger NK cell-mediated "helper" effects on adaptive immunity, shaping T cell responses during different pathological situations through the regulation of DC maturation.